Comparison of a Chaotic Cryptosystem with Other Cryptography Systems - Alshammari, A. S. (Engineering, Technology & Applied Science Research, 2020)
The keyspace of a cryptography system must be long enough in order to protect it from brute force attacks. The One-Time Pad (OTP) encryption is unconditionally secure because of its truly random keystream that is used only once. This paper proposes a new chaotic symmetric cryptosystem approach, comparable to OTP. The proposed system utilizes two Lorenz generators, a main and an auxiliary, where the aim of the second one is to make one of the main Lorenz generator’s parameters to vary continually with time in a chaotic manner. This technique was built on digitizing two Lorenz chaotic models to increase the security level. The scrambling scheme was developed and the Lorenz stream cipher binary stream successfully passed the NIST randomness test. The cryptosystem showed a high degree of security, as it had a keyspace of 2576, and it was compared with existing symmetric key cryptography systems, such as DES, 3DES, AES, Blowfish, and OTP.